Effect of Anodic Mass Transfer in the Electro Winning of Copper in Presence of Organic Compounds - M. El-Kashlan, Howaida; Ahmed, Abdel-Monem (Asian Journal of Chemistry, 2010)
The effect of anodic oxygen bubbles on the rate of mass transfer was studied by measuring the limiting current of deposition of copper from acidified CuSO4 solution using parallel plate cell. Different factors studied as types of inhibitors, their concentration and temperatures. The organic additives used are cysteine, valine, alanine, phenylalanine, serine and threostine. The rate of mass transfer was found to decrease over the natural convection value by an amount ranging from 17.40-54.34 % depending on the types of additives and its concentration. Thermodynamic parameters were also given.